Pendampingan Penerapan Manajemen Pengelolaan Keuangan Masjid Besar Merdeka Wonomulyo Berbasis Aplikasi Sistem Informasi Manajemen Keuangan Singkat Gampang (SIMAKSIGA) - Hasanuddin (Jurnal Pengabdian Masyarakat Formosa, 2022)
This service aims to provide assistance to the administrators of large independent mosques in financial management using a simple application made by Hasanuddin, SE., MM lecturer at the Faculty of Economics and Islamic Business IAI DDI, Polewali Mandar Regency, Quick and Easy Financial Management Information System ( SIMAKSIGA) Community Service is carried out for 5 months starting from January 2022 to May 2022 and the location of the assistance is at the Baitul Maal office of the Merdeka Mosque, Wonmulyo. Financial management that begins with making adjustments to transactions that occur at the mosque, both input and expenditure. The results of the assistance in the form of a short and easy financial management system are expected to assist the management in managing their finances more transparently, and can be held accountable